Complete Service-Learning Courses: The Maturity of a Pedogogy - Ender, Morten (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This section has courses that involve a significant or complete service-learning (SL) feature. The first edition of this volume (Ender, Kowalewski, Cotter, Martin, & DeFiore, 1996) contained no comprehensive SL courses. At the time, the SL and sociology intersection was formative. Five years later, half of the 2nd edition submissions met the comprehensive SL course criteria (Marsteller Kowalewski, Ender, & DeFiore, 2001). SL among sociologists matured. This, the 3rd edition of this ASA best-seller flourishes and shows the 10 year development of SL. For example, Myers-Lipton makes his third contribution and Enos, Knapp, and Sernau make their second. The others are all first time contributors to this the latest edition.